Quadratic Mania!

Algebra Level 3

If m m and n n are the roots of the equation x 2 2 x + 3 = 0 x^2-2x+3=0 , determine the equation whose roots are P = m 3 3 m 2 + 5 m 2 P= m^3-3m^2+5m-2 and Q = n 3 n 2 + n + 5 Q= n^3-n^2+n+5 .

x 2 3 x 2 = 0 x^2-3x-2=0 x 2 3 x + 2 = 0 x^2-3x+2=0 x 2 + 3 x + 2 = 0 x^2+3x+2=0 x 2 + 3 x 2 = 0 x^2+3x-2=0

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Aditya Sky
Mar 27, 2016

Since, m \color{#D61F06}{m} and n \color{#3D99F6}{n} are the roots to the polynomial x 2 2 x + 3 \color{#20A900}{x^{2}-2x+3} , therefore m 2 2 m + 3 = 0 \color{#D61F06}{m^{2}-2m+3=0} and n 2 2 n + 3 = 0 \color{#3D99F6}{n^{2}-2n+3=0} .

By synthetic division, it can be seen that :- ( i ) m 3 3 m 2 + 5 m 2 = ( m 2 2 m + 3 0 ) ( m 1 ) + 1 ( i i ) n 3 n 2 + n + 5 = ( n 2 2 n + 3 0 ) ( n + 1 ) + 2 (i)\,\,\, \color{#624F41}{m^{3}-3m^{2}+5m-2}=(\color{#D61F06}{\underbrace{m^{2}-2m+3}_\text{0}})(m-1)+1 \,\,\,\,\,\,\,\,\,\,\,\ (ii)\,\,\, \color{#624F41}{n^{3}-n^{2}+n+5}=(\color{#3D99F6}{\underbrace{n^{2}-2n+3}_\text{0}})(n+1)+2 m 3 3 m 2 + 5 m 2 = 1 \implies \color{#624F41}{m^{3}-3m^{2}+5m-2}=1 and n 3 n 2 + n + 5 = 2 \color{#624F41}{n^{3}-n^{2}+n+5}=2 .

So, the required polynomial is x 2 ( 1 + 2 ) x + ( 1 2 ) = x 2 3 x + 2 \color{#BA33D6}{x^{2}}-(\color{#624F41}{1+2})\color{#BA33D6}{x}+(\color{#624F41}{1 \cdot 2})\,=\, x^{2}-3x+2 .

nice solution

Vaibhav Gupta - 5 years, 2 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...